Destierro y redención: el «síndrome de Adán y Eva» en La belleza del mundo de Héctor Tizón - Campoy, Emiliano Matías (2024)
In this essay the author establishes a dialogue between the novel La belleza del mundo by Héctor Tizón and the biblical archetypes of Adam and Eve, the loss of paradise and banishment, and the return to Eden. Beginning with the original betrayal of the protagonist’s wife, the integration of a cyclical and infinite time commences-that of banishment–; in exile, the protagonist is marked by his drive to annul real temporality and, at the same time, his own identity; he makes every effort to forget his own history, resulting in an identity crisis. At the end of a long journey the need is established to incorporate the life events with a mythical time that regenerates and perpetuates all the actions, and in which the suffering is sought in order to reach salvation. The author demonstrates the diverse parallelisms of the text with the Christian doctrine: the protagonist understands that in order to return to his own center he must forgive, which is only possible if he returns and confronts his own past: the time of redemption is a return, but the same-new site will never again be considered paradise.